A Glimpse of the genomic diversity of haloarchaeal tailed viruses - Sencilo, Ana; Roine, Elina (Frontiers in Microbiology, 2014)
Tailed viruses are the most common isolates infecting prokaryotic hosts residing hypersaline environments. Archaeal tailed viruses represent only a small portion of all characterized tailed viruses of prokaryotes. But even this small dataset revealed that archaeal tailed viruses have many similarities to their counterparts infecting bacteria, the bacteriophages. Shared functional homologues and similar genome organizations suggested that all microbial tailed viruses have common virion architectural and assembly principles. Recent structural studies have provided evidence justifying this thereby grouping archaeal and bacterial tailed viruses into a single lineage. Currently there are 17 haloarchaeal tailed viruses with entirely sequenced genomes. Nine viruses have at least one close relative among the 17 viruses and, according to the similarities, can be divided into three groups. Two other viruses share some homologues and therefore are distantly related, whereas the rest of the viruses are rather divergent (or singletons). Comparative genomics analysis of these viruses offers a glimpse into the genetic diversity and structure of haloarchaeal tailed virus communities.